A new method for measuring airborne elemental carbon using PUF disk passive samplers. (July 2022) - Zhang, Zheng Wei; Shahpoury, Pourya; Zhang, Wendy; Harner, Tom; Huang, Lin
Abstract: Carbonaceous aerosol species, such as elemental carbon (EC), are important Short-Lived Climate Forcers (SLCFs), contributing to climate and health effects of air pollution. The quantification of carbonaceous aerosols has been conventionally carried out using active air sampling followed by various analytical techniques, such as thermal/thermal-optical analysis. Active sampling requires specific equipment and infrastructure with electricity and therefore may not be the best choice for studying carbonaceous aerosols at remote locations. Passive sampling on the other hand provides a simple and cost-effective alternative to study time-weighted temporal and spatial trends. For the first time in this study, we have developed a method to examine the viability of measuring EC using polyurethane foam passive air samplers (PUF-PAS) coupled with a thermal analysis, i.e., EnCan-Total-900 (ECT9). The method was found reproducible with coefficients of variation as low as 3% for EC measured in ambient passive samples. The method had relatively low background with EC levels in blanks being as low as 0.1% of those in deployed samples, allowing quantification within a wide range of concentrations. The results indicate a homogenous distribution of particles within the PUF-PAS substrate. EC concentrations measured with the passive method were not significantly different from those obtained from active samples at the study sites ( p  > 0.01). This proof of concept of the PUF-PAS method provides an opportunity to cost-effectively expand measurements of elemental carbon at the global scale, and could be further extended to include other carbonaceous aerosol species in the future. This helps address regional data gaps for improving uncertainties of SLCF impacts on global climate forcing and to inform policy decisions. Graphical abstract: Image 1 Highlights: New method to measure ambient elemental carbon using PUF-PAS. Method features good reproducibility and low background contamination. Distribution of elemental carbon within PUF-PAS was homogenous. Elemental carbon concentrations from PUF-PAS were comparable to active samples. Opportunity to expand measurements of elemental carbon globally.